Vocabulary Learning Strategies of Indonesian EFL Undergraduate Students - Utami, Nancy Putri; Daulay, Sholihatul Hamidah (SCOPE: Journal of English Language Teaching, 2024)
Vocabulary is essential in learning a foreign language. This study aims to determine how frequently and how the students feel about the usage of vocabulary acquisition tactics by 22 undergraduate EFL learners. The purposes of this study are achieved by utilizing a descriptive qualitative research methodology. Data for this inquiry were gathered using both questionnaires and observation. Analysis of the interactive simulation developed by Miles and Huberman, which involves data reduction, data display, and conclusion drafting, was the method of data analysis employed in this study. The study's findings show that students use 17 different vocabulary-building strategies. The vocabulary acquisition strategies that the students in this study selected and used were significantly influenced by their teaching and learning environment, culture, learning preferences, and sources of motivation. Every student has a different learning style that they find most effective in increasing their vocabulary as well as vocabulary.